2015
DOI: 10.1152/ajpheart.00405.2015
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous ventricular tachyarrhythmias in β2-adrenoceptor transgenic mice in relation to cardiac interstitial fibrosis

Abstract: Myocardial fibrosis is regarded as a pivotal proarrhythmic substrate, but there have been no comprehensive studies showing a correlation between the severity of fibrosis and ventricular tachyarrhythmias (VTAs). Our purpose was to document this relationship in a transgenic (TG) strain of mice with fibrotic cardiomyopathy. TG mice with cardiac overexpression of β2-adrenoceptors (β2-AR mice) and non-TG (NTG) littermates were studied at 4-12 mo of age. VTA was quantified by ECG telemetry. The effect of pharmacolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(61 citation statements)
references
References 46 publications
3
56
0
2
Order By: Relevance
“…Cardiac Gal‐3 content is increased in β 2 ‐TG mice at a young age and then it progressively increases with ageing in parallel to the progression of cardiomyopathy, myocardial fibrosis, and inflammation (Nguyen, Su, Kiriazis, et al, ; Xu et al, ). Thus, the progressive increase in cardiac Gal‐3 content in this model is likely to be attributable to the age‐dependent increase in the cardiac densities of inflammatory cells and fibroblasts (Nguyen et al, ; Nguyen, Su, Vizi, et al, ).…”
Section: Gal‐3 As a Biomarker Of Heart Disease: Influence Of β‐Adrenomentioning
confidence: 97%
“…Cardiac Gal‐3 content is increased in β 2 ‐TG mice at a young age and then it progressively increases with ageing in parallel to the progression of cardiomyopathy, myocardial fibrosis, and inflammation (Nguyen, Su, Kiriazis, et al, ; Xu et al, ). Thus, the progressive increase in cardiac Gal‐3 content in this model is likely to be attributable to the age‐dependent increase in the cardiac densities of inflammatory cells and fibroblasts (Nguyen et al, ; Nguyen, Su, Vizi, et al, ).…”
Section: Gal‐3 As a Biomarker Of Heart Disease: Influence Of β‐Adrenomentioning
confidence: 97%
“…Myocardial fibrosis was determined by hydroxyproline assay as previously described (Nguyen et al, 2015). An apical portion of the LV (about 20 mg) was used for the assay with hydroxyproline values converted into total collagen content.…”
Section: Hydroxyproline Assay For Collagenmentioning
confidence: 99%
“…Progression of cardiomyopathy in the TG model is age‐dependent measured by phenotypes of ventricular dilatation, dysfunction, spontaneous VTA and premature deaths 17‐19 . In this study, mice aged at 9‐10 months were used, because TG mice at this age exhibit severe cardiomyopathy with frequent onset of VTA 7 . There is strong evidence for a relationship between fibrosis and arrhythmogenesis 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study showed that the β 2 ‐adrenoceptor ( β 2 ‐AR) transgenic mice (TG) exhibited an age‐dependent development of cardiomyopathy featured by fibrosis, ventricular remodelling, dysfunction, VTA and premature deaths 7 . In this model, the frequency of ventricular ectopic beats (VEBs) and episodes of VT recorded by telemetry is increasing with age: approximately 1000 per hour for VEB and 80 episodes per hour for VT were recorded in TG mice aged 9–11 months 7 . Thus, even a 10‐minute period of ECG recording allows for quantitative evaluation of the severity of VTA …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation